Unlocking the nutritional potential: amino acid profile of eight Indian food fishes and their role in meeting recommended dietary allowances - Das, Basanta Kumar; Kumari, Kajal; Ganguly, Satabdi; Talukder, Anjon Kumar; Ray, Archisman; Dutta, Subhamoy; Baisakhi, Barsha (Frontiers in Sustainable Food Systems, 2024)
Proteins and amino acids, as vital biomolecules, are not only part of key metabolic pathways in the body but are also essential for tissue repair, enzyme function, and hormone regulation.They also serve as building blocks for the formation of signalling molecules, such as neurotransmitters and catecholamines. Additionally, amino acids are the primary building components of proteins. Fish serves as a vital source of high-quality animal protein and amino acids, playing a crucial role in supporting human nutrition. The present study investigated the amino acid content of eight food fishes from diverse aquatic habitats by high-performance liquid chromatography (HPLC) using fluorescence detector. The study revealed that the small indigenous fish (SIF) Systomus sarana and the marine fish Sardinella melanura were rich sources of all essential amino acids. Furthermore, estuarine fish like Pisodonophis boro can be recommended for specific amino acids like arginine, histidine, leucine, and valine, while Setipinna phasa is suggested for cysteine. These recommendations rely on the possible contribution of these fishes to the Recommended Dietary Allowance (RDA) regarding each nutrient. The insights gained from this study could be utilised as recommendations to meet amino acid requirement using fish as a natural supplement.